2009
DOI: 10.1093/eurpub/ckp065
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of family violence in adults and children: estimates using the capture–recapture method

Abstract: CRC appears to be a valid and feasible research method for estimating the prevalence of family violence and child abuse. It can be used to complement other methods, especially in young children, in whom valid results are otherwise difficult to obtain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…One of the most common methodological approaches for collecting maltreatment data involved the use of retrospective adult self-reports of childhood experiences [ 28 ]. Some researchers have raised concerns about the reliability and validity of retrospective recall in adult respondents, especially about childhood events and about events that are emotionally charged [ 29 ], what is known as recall bias [ 12 , 30 , 31 ]. Concerns include forgetting an experience that happened many years ago [ 32 ], while length of time since the abuse occurred may impact reliability [ 33 ], and adults maltreated as children may experience memory impairment related to the event [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most common methodological approaches for collecting maltreatment data involved the use of retrospective adult self-reports of childhood experiences [ 28 ]. Some researchers have raised concerns about the reliability and validity of retrospective recall in adult respondents, especially about childhood events and about events that are emotionally charged [ 29 ], what is known as recall bias [ 12 , 30 , 31 ]. Concerns include forgetting an experience that happened many years ago [ 32 ], while length of time since the abuse occurred may impact reliability [ 33 ], and adults maltreated as children may experience memory impairment related to the event [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gathering data on maltreatment using formally collected data only can be problematic because of the sole reliance on system indicators, created for bureaucratic and tracking purposes as opposed to research purposes [ 11 ], although formally reported cases are likely to represent more serious episodes. Even when data are collected from several different organisations and combined, this is likely to be an underrepresentation [ 12 ], due to underreporting. Fallon et al (2010) note that how a child maltreatment event is measured will affect counts of maltreatment cases by agencies.…”
Section: Introductionmentioning
confidence: 99%
“…Some rates are probably an underestimation because of the reluctance of some people to report abuse (Cooper et al 2008). Oosterlee et al (2009) estimate that only 20% of victims are known to one or more organisations, whilst O' Keeffe et al (2007) estimate that only 3% of cases are known to the lead agency for adult protection, social services, in the UK. Valid and reliable measurement instruments are needed (Cooper et al 2008).…”
Section: Future Researchmentioning
confidence: 99%
“…Only two women reported that FV was their reason for being at the hospital. As shown in the previous studies, only a few victims report this kind of violence . Men and women are most likely to seek support for violence from family and friends rather than from institutions or organisations.…”
Section: Discussionmentioning
confidence: 70%